The effectiveness of approach group counseling services traits and factors to increase maturity student career - Agungbudiprabowo Agungbudiprabowo; Wahyu Nanda Eka Saputra; Siti Rohimatul Auliyah; Hardi Prasetiawan; Ariadi Nugraha (Universitas Negeri Padang, 2021)
Career maturity is a very important thing for teenagers to have because career maturity, that is, individuals have understood of themselves which includes their interests and talents as well as their capacities. This study aims to determine the effectiveness of group counseling services using the trait and factor approach to increase student career maturity. This type of research is quantitative with the pre-experimental one-group pretest and posttest methods. The population taken in this study was all class XII both science and social studies with a total of 288 students. Then the sample used in this study was class XII IPS 2, where as many as 5 students were taken using a purposive sampling technique taken in a low category, which was then carried out by group counseling services. This research instrument uses a career maturity scale that has been tested for validity and reliability. In addition, researchers used observational decision-making instruments in this study using the normality test and SPSS version 24-assisted T-test. The results of this study are based on the results of hypothesis testing using the t-test obtained sig (2-tailed) = 0.000 then compared with the alpha value (α ) 5% = 0.05 provided that the sig (2-tailed) value is less than the alpha (α) value of 5% (0.000 ≤ 0.05), then it can be said that Ho is rejected and Ha is accepted. So it can be concluded that group counseling services using the trait and factors approach are effective in increasing the career maturity of students at SMAN 5 Yogyakarta. The results of the study can be used as a reference for guidance and counseling teachers in schools in developing students' career maturity using career counseling traits and factors.